Projecting biodiversity benefits of conservation behavior‐change programs. Issue 3 (10th January 2022) - Selinske, Matthew J.; Bekessy, Sarah A.; Geary, William L.; Faulkner, Richard; Hames, Fern; Fletcher, Charlotte; Squires, Zoe E.; Garrard, Georgia E.
Abstract: Biodiversity loss is driven by human behavior, but there is uncertainty about the effectiveness of behavior‐change programs in delivering benefits to biodiversity. To demonstrate their value, the biodiversity benefits and cost‐effectiveness of behavior changes that directly or indirectly affect biodiversity need to be quantified. We adapted a structured decision‐making prioritization tool to determine the potential biodiversity benefits of behavior changes. As a case study, we examined two hypothetical behavior‐change programs––wildlife gardening and cat containment––by asking experts to consider the behaviors associated with these programs that directly and indirectly affect biodiversity. We assessed benefits to southern brown bandicoot ( Isoodon obesulus) and superb fairy‐wren ( Malurus cyaneus ) by eliciting from experts estimates of the probability of each species persisting in the landscape given a range of behavior‐change scenarios in which uptake of the behaviors varied. We then compared these estimates to a business‐as‐usual scenario to determine the relative biodiversity benefit and cost‐effectiveness of each scenario. Experts projected that the behavior‐change programs would benefit biodiversity and that benefits would rise with increasing uptake of the target behaviors. Biodiversity benefits were also predicted to accrue through indirect behaviors, although experts disagreed about the magnitude of additional benefit provided. Scenarios that combined the two behavior‐change programs were estimated to provide the greatest benefits to species and be most cost‐effective. Our method could be used in other contexts and potentially at different scales and advances the use of prioritization tools to guide conservation behavior‐change programs. Abstract : Article impact statement : Structured decision‐making shows human behavior‐change interventions' potential impact on biodiversity and relative cost‐effectiveness. Abstract : Proyección de los beneficios para la biodiversidad obtenidos de los programas de cambios de comportamiento de conservación Resumen: La pérdida de la diversidad biológica es causada por el comportamiento humano, pero existe incertidumbre sobre la efectividad que tienen los programas de cambio de comportamiento para otorgar beneficios a la biodiversidad. Para demostrar el valor que poseen, los beneficios para la biodiversidad y la rentabilidad de los cambios de comportamiento que afectan directa o indirectamente a la biodiversidad necesitan ser cuantificados. Adaptamos una herramienta de priorización de toma de decisiones estructurada para determinar el potencial de los beneficios para la biodiversidad obtenidos de los cambios de comportamiento. Como estudio de caso, examinamos dos programas hipotéticos de cambio de comportamiento, la jardinería silvestre y la contención de gatos, mediante la petición a expertos de considerar los comportamientos asociados con estos programas que directa o indirectamente afectan a la biodiversidad. Evaluamos los beneficios para el bandicut café ( Isoodon obeselus ) y el reyezuelo supremo ( Malurus cyaeneus ) mediante la obtención de estimaciones de expertos de la probabilidad de que cada especie persista en el paisaje con una gama establecida de escenarios de cambios de comportamiento en los cuales la aceptación de los comportamientos varió. Después comparamos estas estimaciones con un escenario de situación normal para determinar el beneficio relativo para la biodiversidad y la rentabilidad de cada escenario. Los expertos proyectaron que los programas de cambio de comportamiento beneficiarían a la biodiversidad y que los beneficios aumentarían con la creciente aceptación de los comportamientos deseados. También se pronosticó que los beneficios se acumularían mediante comportamientos indirectos, aunque los expertos estuvieron en desacuerdo sobre la magnitud del beneficio adicional proporcionado. Se estimó que los escenarios que combinaron los dos programas de cambio de comportamiento proporcionarían el mayor beneficio para las especies y serían los más rentables. Nuestro método podría usarse en otros contextos y potencialmente a diferentes escalas y fomenta el uso de herramientas de priorización para orientar a los programas de cambios en el comportamiento de conservación. 预测保护行为改变项目的生物多样性效益: 【摘要】 人类行为驱动了生物多样性的丧失, 但通过行为改变项目使生物多样性获益的效果尚不明确。为证明行为改变项目的价值, 则需要定量评估直接或间接影响生物多样性的行为改变产生的生物多样性效益和成本效益。本研究采用一种结构化决策优先级工具, 确定了行为改变的潜在生物多样性效益。我们通过两个模拟的行为改变项目(野生动物园艺和家猫控制)作为案例研究, 要求专家评估与这些项目相关的直接及间接影响生物多样性的行为。我们通过向专家咨询在采取不同程度的行为改变所产生的一系列行为改变情景下每个物种在景观中续存的概率, 评估了行为改变对棕短鼻袋狸( Isoodon obesulus )和壮丽细尾鹩莺( Malurus cyaneus )的好处。接下来, 我们将这些估计情况与"一切照旧"的情景进行对比, 以确定每种情景的相对生物多样性效益和成本效益。根据专家预测, 行为改变项目将有益于生物多样性, 且随着人们对目标行为的接纳度增加, 生物多样性的效益也会提升。我们还预计生物多样性效益会通过间接行为得到累积, 尽管关于该额外效益程度的专家意见仍有分歧。此外, 我们估计在两种行为改变项目相结合的情景中, 物种获得的利益和成本效益都最高。我们的方法还可以用于其他背景或尺度, 以推动优先级工具在指导保护行为改变项目中的应用。【翻译: 胡怡思; 审校: 聂永刚】